Benefit of Platinum-based Chemotherapy in Metastatic Triple Negative Breast Cancer - Ency Eveline; Andhika Rachman (PT. Kalbe Farma Tbk., 2015)
Background. Management of triple-negative breast cancer (TNBC) is challenging because of a lack of targeted therapy, its aggressive behavior and relatively poor prognosis. Various studies showed that these tumors are highly chemosensitive and in some cases are represented by complete pathological response (pCR), but the results remains unsatisfactory1. Recent experimental data strongly suggest that platinum-based chemotherapy (PBC) could improve the outcome of TNBC, but clinical data is still lacking4. Objective. To evaluate the benefit of addition of platinum agents to metastatic TNBC therapy. Method. Several databases were searched. Comparative studies were identified using the following keywords: triple negative breast cancer, advanced, metastatic, metastases, platinum agents, cisplatin, and carboplatin. The search was not limited to controlled or randomized trials. The limitation used in searching the articles are human, english, and max.5 years publication. Articles were reviewed by two authors and selected if they described advanced triple negative breast cancer, use of platinum agents, and outcome. Results. Seven studies were included. Median survival of metastatic TNBC patients treated with PBC was 10.4 to 32.8 months. There was a significant survival benefit compared to non-PBC treated patients with overall survival 7.5 to 21.5 months. However PBC did not showed significant different benefit between TNBC and non TNBC patients. Conclusion. PBC demonstrated not only higher response rate but also remarkable improvement in PFS and OS. It is still premature to draw a conclusion on survival advantage merely from phase II trials, but for this subtype, platinum agents had extra clinical benefit compared to other agents.Pendahuluan. Topik Manajemen triple-negative breast cancer (TNBC) masih merupakan sebuah tantangan karena ketidaktersediaan target terapi hormonal, sifatnya yang agresif, dan prognosis yang lebih buruk. Beberapa studi menyimpulkan bahwa tumor ini sangat kemosensitif sehingga pada beberapa kasus menghasilkan complete pathological response (pCR), tetapi makna klinisnya kurang berarti1. Meskipun data eksperimental secara kuat mendukung platinum-based chemotherapy (PBC) sebagai kemoterapi yang dapat memperbaiki outcome TNBC, belum ada data studi klinis. Tujuan penelitian ini ialah untuk mengevaluasi manfaat penambahan agen platinum sebagai terapi pasien TNBC stadium lanjut. Metode. Beberapa database ditelusuri, Kata kunci yang digunakan: triple negative breast cancer, advanced, metastatic, metastases, platinum agents, cisplatin, dan carboplatin. Pencarian tidak dibatasi hanya controlled atau randomized trials untuk meminimalkan hilangnya studi yang bermakna. Pencarian artikel dibatasi pada human subject, english, dan max.5 years publication. Artikel dianalisis oleh dua penulis dan diseleksi sesuai dengan TNBC stadium lanjut, penggunaan agen platinum, dan hasil terapi. Hasil. Median survival empat studi yang ditemukan berada dalam rentang 10.4 hingga 32.8 bulan. Terdapat manfaat cukup signifikan dari penambahan agen kemoterapi platinum sebagai terapi pasien TNBC stadium lanjut, dibandingkan regimen tanpa platinum yang berada dalam rentang 8 hingga 21.5 bulan. Akan tetapi tidak ada perbedaan klinis penggunaan PBC antara pasien TNBC dan non-TNBC. Simpulan. PBC menghasilkan bukan hanya tingkat respon lebih tinggi tetapi juga perbaikan PFS dan OS. Meskipun belum adekuat untuk menyimpulkan adanya perbaikan survival pasien TNBC, platinum lebih memberikan perbaikan klinis daripada agen kemoterapi lain.